Pattern of Ocular Morbidity in Professional Intercity Vehicle Drivers of MidWest Tarai Belt of Nepal: A Cross Sectional Descriptive Study - Bastola, P (Journal of Nepalgunj Medical College, 2015)
Background: Visual function is very important in driving. The diseases of the ocular organs and its adnexa can adversely affect the visual functions of the driver, resulting into serious implications in road safety. Aim: Finding out the profile and pattern of ocular morbidity in professional intercity vehicle drivers of Mid West Tarai region of Nepal. Methodology: This was a cross sectional, descriptive, community/hospital based study carried out in two of the busiest bus parks of Mid West Tarai region of Nepal. All professional drivers with a valid government driving license who had been driving as professional drivers for more than 3 months were enrolled. Results: Of the 256 participants in the study, all of the professional drivers were males. In 162 (66.4%) of the study participants did not have ocular examination before issuing or during renewal of the driving license. More than 50% of ocular morbidity was due to dry eyes, ocular allergy, uncorrected refractive error and conjunctival degenerative conditions in all age groups. Presbyopia and cataract in subjects above 40 years accounted for 34 (13%) and 10(3.9%) respectively. 16(6.2%) of study participants were still driving with valid license despite having total color blindness. Conclusions: Every potential driver at first licensing and at renewals should be subjected to basic vision tests. Color vision test should be made prerequisite for all the drivers before issuing a government license. Those found to have visual impairment should be referred to ophthalmologists for detailed ocular evaluation and periodicocular examination. Journal of Nepalgunj Medical College Vol.12(1) 2014: 14-18